Pacific affairs. - University of British Columbia; Institute of Pacific Relations (Vancouver University of British Columbia, 1928)
Includes book reviews and bibliographies.
Issues for Feb.-Dec. 1929 called also no. 2-12; issues for Jan. 1930- called also v. 3, no. 1-
Full-text scanned reproductions of back issues of this publication are available to subscribing institutions via the JSTOR World Wide Web site.
Also issued on microform.
Published by: Institute of Pacific Relations May 1928-Dec. 1960; UBC, spring 1961-
Keywords: Institute of Pacific Relations -- Periodicals; Pan-Pacific relations -- Periodicals; Pan-Pacific relations; Pan-Pacific relations -- Periodicals; PACIFIC OCEAN REGION; ASIA; PAN-PACIFIC RELATIONS; Computer network resources; Periodicals